Implementation of electronic certificates and online land registration systems in realizing efficient land services - Wirda Ningsih Octavia (Priviet Social Sciences Journal, 2026)
The digital transformation in Indonesia's land system marks a significant paradigm shift from manual systems to integrated electronic systems. This study examines the implementation of electronic certificates and online land registration systems in the context of sale and purchase deeds made by Land Deed Making Officials (PPAT). The main issues studied include: (1) how Indonesia's positive legal framework regulates the digital transformation of land sale and purchase deeds and electronic certificates; (2) legal challenges and obstacles in the implementation of land electronic systems, including aspects of legal certainty, data security, and protection of community rights; and (3) the ideal model for the implementation of digital transformation that can realize efficient land services without sacrificing legal certainty. The research uses a normative juridical method with a statute, case, and theoretical approach. The results of the study show that Indonesia's legal framework has accommodated digital transformation through the ITE Law, PP 24/1997 jo. PP 18/2021 on Land Registration, and other related regulations. However, implementation faces challenges in the form of gaps in technological infrastructure, human resource readiness, system standardization, and regulatory harmonization. The recommended ideal model is phased implementation with strengthened cybersecurity aspects, integrated digital validation, a reliable backup system, and comprehensive legal protection for the parties. Digital transformation must guarantee the principles of publicity, legal certainty, and the protection of human rights in land ownership.